PENGOLAHAN FROZEN IKAN UNTUK MENINGKATKAN KUALITAS DAN NILAI EKONOMI MASYARAKAT PESISIR - Afiat, Muhammad Nur; Asizah, Nur; Gamsir, Gamsir; Nusantara, Ambo Wonua; Lapipi, Lapipi; Dewangga, Puspa; Nur, Syamsir; Saenong, Zainuddin (Jurnal Pengabdian Masyarakat Sabangka, 2025)
This community service program aims to empower the coastal community of Wowanggu Subdistrict, Kendari City, through training on processing fish into value-added products such as marinated and original frozen fish. The implementation method uses a participatory approach combining technical training (processing, packaging, storage) and business management (financial recording, digital marketing). Participants consisted of 16 people, predominantly housewives (38%), fish traders (30%), and young entrepreneurs (11%). Evaluation results showed significant improvement in participants' understanding, with 72% strongly agreeing on the training benefits, particularly in business management and entrepreneurial motivation. The main challenges were raw material availability and capital. The program successfully created positive impacts by enhancing skills and entrepreneurial interest, while opening opportunities for fisheries-based SME development in coastal areas.